Description of two new Megistophylla Burmeister, 1855 species from China, with a redescription of M. andrewesi Moser, 1913 (Coleoptera: Scarabaeidae: Melolonthinae) - Wang, Fa-Lei; Li, Yan-Long; Gao, Chuan-Bu (Zootaxa, 2024)
This study presents descriptions and illustrations of two new melolonthine species: Megistophylla brevivirgata Wang & Gao, new species and M. keithi Wang & Gao, new species from Yunnan province in China. Additionally, a detailed redescription and illustration of the male of M. andrewesi Moser, 1913, and a description of its previously unknown female are provided. Finally, a key to identification of Megistophylla Burmeister, 1855 species from China is added.